Fazer-se multidão: multiplicidade, classe e comum - Bruno Tarin (Universidade do Vale do Rio dos Sinos (UNISINOS), 2017)
This article is devoted to studies on the concept of multitude. In order to support the analyzes and elaborations on this concept, the article begins with a brief reflection on how the idea of large groups or collective subject has been seen throughout history, with emphasis on the period of the philosophical and political formation of the sovereign States (16th century) and the period of formation of those that became known as mass societies (19th century). Concluding the first session of this article, we recognize the reemergence of the multitude at the turn of the late 20th century to the beginning of the 21st century, when the debate about the multitude reappears and the extremely negative contours that the notion assumed predominantly in previous periods begins to be gradually dismantled. The multitude, in its making itself, thus reemerges as a device capable of opposing the Empire. To access this capacity of the multitude, we analyze especially the propositions of Antonio Negri in three main axes: the multitude while multiplicity, and while class and its relation with the common.